Preparation of novel phosphor using intercalation of tobermorite - Kojima, Yoshiyuki; Kamei, Shinnosuke; Toyama, Takeshi; Nishimiya, Nobuyuki (Journal of luminescence, 2009)
The emission intensity of phosphors is often subject to concentration quenching after doping of the activator in the host crystal rises above a certain limit. This study describes the preparation of novel phosphors based on tobermorite that do not exhibit concentration quenching. In the preparation of phosphors, Eu 3+ ions are exchanged with intercalated Ca 2+ ions within the tobermorite by dipping in EuCl 3 solution. The emission intensity of the Eu 3+ doped tobermorite increased with increasing Eu/Ca atomic ratio and attained a maximum value of 8.6% for a Eu/Ca atomic ratio of 0.22. Heating of the phosphor at 800 °C resulted in a three-fold improvement in emission intensity.